The Relationship Between Dietary Patterns, Nutritional Knowledge, and Early Marriage With the Incidence of Chronic Energy Deficiency Among Pregnant Women - Asnawati; Yanti, Rusmini; Nurhamidi; Magdalena (Jurusan Gizi Poltekkes Kemenkes Banjarmasin, 2026)
Stunting is a chronic nutritional problem in toddlers that remains prevalent and can be influenced by factors starting from pregnancy until the child’s history of illness. This study aimed to determine the relationship between low birth weight (LBW), maternal nutritional status during pregnancy, and history of infectious diseases with the incidence of stunting among toddlers aged 6–59 months in the work area of UPTD Puskesmas Wanaraya. This research used an analytic observational method with a cross-sectional design. The study population consisted of 727 toddlers, with a total sample of 125 toddlers selected using proportionate sampling. The dependent variable was stunting incidence, while the independent variables were LBW, maternal nutritional status during pregnancy (CED based on MUAC), and infectious disease history (illness within the last month). Data were analyzed using the Spearman Rank test with α = 0.05. The results showed that 44.8% of toddlers were stunted and 55.2% were not stunted. Toddlers with a history of LBW were 9.6%, mothers with CED history during pregnancy were 35.2%, and toddlers with a history of infectious diseases were 47.2%. Statistical analysis indicated no relationship between LBW and stunting (p = 0.325), and no relationship between maternal nutritional status during pregnancy and stunting (p = 0.631). However, there was a relationship between infectious diseases and stunting (p = 0.018). It is expected that parents improve prevention and management of infectious diseases in toddlers to reduce the risk of stunting.